Efektivitas Metode Pembelajaran Cooperative Script Dalam Meningkatkan Keterampilan Berbicara Teks Negosiasi Siswa Kelas X SMK Nassional Berbah - Elsa Zudianingrum; Nina Widyaningsih (sarasvati, 2026)
This research was motivated by the low speaking skills of students in negotiation text learning, such as lack of confidence in expressing opinions, passive participation during discussions, and limited opportunities to practice speaking. This study aimed to determine the differences in students’ speaking skills between classes using the Cooperative Script learning method and classes not using the method, as well as to determine the effectiveness of the Cooperative Script method in improving negotiation text speaking skills of tenth-grade students at SMK Nasional Berbah. This study used a quantitative approach with a quasi-experimental research design and a Pretest-Posttest Control Group Design. The population consisted of tenth-grade students of SMK Nasional Berbah, with a sample of 56 students divided into an experimental class and a control class. Data collection techniques included observation, tests, questionnaires, and documentation. Data were analyzed using normality tests, homogeneity tests, and t-tests with the assistance of SPSS 26 software. The results showed that the Cooperative Script learning method was effective in improving students’ speaking skills in negotiation text learning. This was indicated by the posttest mean score of the experimental class, which was 85.43, higher than the control class score of 67.68. In addition, the normality test results showed that the data were normally distributed, indicating that the statistical analysis requirements were fulfilled. Therefore, the Cooperative Script method can be used as an alternative learning method to improve students’ activeness and speaking skills in negotiation text learning.